Динамічне дослідження механізму просівання формувальної землі - Зінченко, Олена Іванівна (НТУ "ХПІ", 2008)
In the article method of dynamical analysis of mechanisms of screening forming earths with application analytical method and by means approximate of spline are considered
Keywords: ланка; сито; рух; машина; енергія; центр мас